Implementation of Total Quality Management - Ibrahim; Nazmul Hoque, Muhammad; Darusalam (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study aims to analyze integrated quality management and the importance of implementing integrated quality management in schools. The research focuses on two aspects: (1) The implementation of integrated quality management, and (2) The factors that support and hinder integrated quality management. This research was conducted at SMA Negeri 1 Rambutan in Banyuasin Regency, using a descriptive qualitative research method. The informants in this study included the school principal, administrative staff, teachers, parents, and students. Data was obtained through observation, interviews, and documentation. The data analysis method includes data reduction, data presentation, and drawing conclusions, while the validity of the data in this study was ensured using source triangulation and technique triangulation. Based on the findings, the implementation of integrated quality management has been carried out well; however, there are still areas that need to be improved continuously across various fields each year. With the implementation of this integrated quality management, it is hoped that SMA Negeri 1 Rambutan will become a quality school capable of competing with other schools. Schools must apply the concept of integrated quality management in the future, focusing on the implementation of sustainable quality management principles, involving all components of the school, and being responsive to technological developments and the future needs of education.